(untitled) - Chaffee, Clarence (Hoboken, N.J., 2008)
The purpose of this book is to clear up that confusion. It gives you just the information that you need to know about the exam, and the steps that you need to take to sign up for the test, study for this test, and pass this test. When you complete this book, you will understand everything that you need to know about the L.A.R.E. You will have the information and the tools you need to prepare for the test in a manner that will maximize your chances of passing.
Keywords: Landscape architecture,Landscape architecture,Kiến trúc cảnh quan,Kiến trúc cảnh quan; Examinations,Examinations,Khảo sát,Khảo sát; Hướng dẫn nghiên cứu; United States,Canada,Hoa Kỳ,Canada